(untitled) (Revista Sistemas de Producción Agroecológicos, 2013)
This work was made with the objective to evaluate the productive, nutritional and economic behavior in laying Japanese quails (Coturnix coturnix japonica) of week 2 to 23 of laying, using meal of leaf of mulberry (Morus alba) in three leaves the substitution the commercial concentrated. 128 birds of 52 days of age were used. Completely randomized design, with four treatments (0, 10, 15 and 20% of meal of leaf of mulberry T1, T2, T3 and T4, respectively), each one with four repetitions and 8 birds by cage. Was not significant difference between the witness (T1) and the T3, in percentage of posture, food intake g/bird/day, conversion kg feed/kg eggs produced and conversion kg feed/dozen eggs produced. (P>0.05), It was observed significant difference of the weight of eggs (P<0.001) between the four treatments. The biological test for protein efficiency, showed to significant differences (P<0.001) between the T4 and the other three treatments, as far as the biological value of proteins was not significant difference (P>0.05). The best economic yield, relation benefit/cost and price by kilogram of diet, were the reported ones for the T3, following of the T1, T2 and finally the T4. The productive, nutritional and economic results, found in this work, allow to conclude that the best treatment is the one that contains 15% of mulberry leaf flour (Morus alba) in replacement of the commercial concentrated, and that is not recommendable to arrive available until a level of 20%, because the production diminishes.